Behavior of ultra-high performance fiber reinforced concrete columns under pure axial loading. (15th September 2015) - Hosinieh, Milad Mohammadi; Aoude, Hassan; Cook, William D.; Mitchell, Denis
Highlights: Six UHPFRC columns with varying tie spacing and configuration are tested. Reducing tie spacing is found to improve column confinement and ductility. Improving cross-section detailing is found to improve confinement and ductility. Fibers in UHPFRC allowed for gradual spalling and high damage tolerance. Column responses are predicted using existing HSC and FRC confinement models. Abstract: This paper presents the results of a study examining the axial load performance of ultra-high performance fiber reinforced concrete (UHPFRC) columns. As part of the experimental program six large-scale columns were tested under pure axial loading to examine the effect of UHPFRC and transverse reinforcement detailing on column performance. The results demonstrate that the provision of closely-spaced and well-detailed transverse reinforcement allows for the development of excellent ductility in UHPFRC columns. The results also indicate that spacing and configuration of transverse reinforcement are important factors affecting the axial strength and toughness of UHPFRC columns. The analytical investigation examines the suitability of using existing high-strength concrete and fiber reinforced concrete confinement models to predict the axial response of the columns tested in this research program. The results indicate the need for the development of UHPFRC-specific confinement models.